Tradisi Puasa Al-Ayyam Al-Bidh di Pondok Pesantren Wali Songo Situbondo - Umi Nuriyatur Rohmah (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
Living Hadis is a phenomenon of practice, tradition, ritual or behavior living in a society based on the rules of the Prophet Muhammad; this article is one of the practices of living hadis in Wali Songo Islamic Boarding School concerning the al-ayyam al-bidl fasting tradition. The practice departs from hadith's understanding of the al-ayyam al-bidl fasting advice (on white days, 13th, 14th, 15th, every hijri month). The focus of this study is to know the practice and history of the implementation of al-ayyam al-bidl fasting and explore how the santri and the society around Wali Songo Islamic Boarding School interpret the implementation of al-ayyam al-bidl fasting. This research is descriptive, that is to explain the living hadis in Wali Songo Islamic Boarding School systematically. The approach of this study is phenomenology. This study concluded that, first, the al-ayyam al-bidl fasting tradition is carried out by all santris of Wali Songo and the local society, that fast has been carried out since the establishment of Wali Songo Islamic Boarding School in 1993. On the third day of fasting, the Wali Songo Islamic Boarding School leader invites the santri and the society to break their fast together at one of the beaches in Situbondo and continue with the Maghrib and Isya’ prayer in a congregation. Secondly, the al-ayyam al-bidl fasting is one of the proofs of love for the Prophet by carrying out his sunnahs because the sunnah is not only known but also carried out. In addition, it is also a means to strengthen solidarity between santri and society.